HUBUNGAN KADAR NATRIUM DENGAN ANGKA KEMATIAN DALAM 30 HARI PADA INFARK MIOKARD AKUT (TINJAUAN PUSTAKA DAN LAPORAN HASIL PENELITIAN) - , Eko Bacharibjatoen, Dr. Bambang Irawan SpPD-KKV SpJP(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Coronary heart disease is a progressive disease, characterized by var iety of clinical presentations from asymptomatic, stable angina, acute coronary syndrome and suddent death. In acute miocard infarct, release of nonosmotic vasopressin on the state of acute left ventricular dysfunction occurs in respon to bone pain, nausea, stress, or respon to analgetic and diuretic. Rate of vasopresin mount concurrently with activation of other neurohormonal like and rennin of norepinephrine. Patient with acute miocard infarct, hiponatremia become very low caused by activation at the same time from rennin angiotensin system and increase catecolamin. Low sodium level represent of activation of neurohormonal in acute miocard infark was high risk to heart failure and mortalitas. Objective: To know relationship between early sodium level and mortality within 30 day in acute myocardial infarction. Methods: This study is an observational prospective cohort study in AMI patients who treated in Intensive Cardiac Care Unit (ICCU) of Dr. Sardjito Hospital since October 2005 to September 2006.. Subject fulfilled inclusion and exclusion criteria , divided into 2 group, group with sodium < 136 mEq/L and sodium â¥136 mEq/L. Time of collecting sampling on sodium was on admission hospital. During 30 days of follow up, we observed outcome of mortality. Results: There were 47 subjects, they consist of 34 males and 13 females. Mortality outcome in group sodium > 136 mEq/L was higher than sodium â¥ 136 mEq/L (p=0,0154). Survival analisis with Kaplan-Meier methode to mortality showed there was significantly difference between two groups ( log rang p=0,036). Conclusions: Low serum sodium level affect the mortality during 30 days of follow up post AMI events with odds ratio 3,422 (95% CI: 0,761-15,388